Are Chinese Individuals prone to Money Illusion? - Heleen Mees; Philip Hans Franses (Tinbergen Institute, 2011)
Using a unique dataset collected through a well-established survey, which was carried out in China, we examine whether Chinese individuals are prone to money illusion. In contrast to the outcomes for US individuals, we find that the Chinese are more likely to base decisions on the real monetary value of economic transactions. We put these observed differences in findings in perspective by comparing the economic conditions in the US and China.
urn:NBN:nl:ui:15-1765/26792
Keywords: E30; E40; 330; Money illusion; Geldillusion; Preisstabilität; Meinung; Vergleich; China; USA